2020
DOI: 10.31234/osf.io/csr3u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why has the COVID-19 pandemic increased support for Universal Basic Income?

Abstract: The 2020 global COVID-19 pandemic has led to a marked increase in positive discussion of Universal Basic Income (UBI) in political and media circles. However, we do not know whether there has been a corresponding increase in support for the policy in the public at large, or why. Here, we present two studies carried out in April and May 2020 in UK and US samples. In study 1 (n=802), we find that people express much stronger support for a UBI policy for the times of the pandemic and its aftermath than for normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…Building on the literature postulating that people facing difficulties keep resources to themselves rather than sharing them with others (Hobfoll, 1989), we predicted and found that AFS was positively related to support Universal Basic Income (Nettle et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Building on the literature postulating that people facing difficulties keep resources to themselves rather than sharing them with others (Hobfoll, 1989), we predicted and found that AFS was positively related to support Universal Basic Income (Nettle et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Participants read a definition of the Universal Basic Income and stated their support for this idea ("How bad or good an idea would it be to introduce a Universal Basic Income in your country?") on a sliding scale ranging from 0 = Bad idea to 100 = Good idea (Nettle et al, 2020).…”
Section: Short Form Of the State-trait Anxiety Inventory (Stai)mentioning
confidence: 99%
“…There are three crucial reasons for rejecting Martinelli’s conclusions. First, perceptions of public spending have been transformed by the pandemic (Nettle, Johnson, Johnson & Saxe 2021 ), in which greatly enhanced public spending has become the norm. This extends even to governments, including in the UK, that have traditionally been committed to fiscal conservatism.…”
Section: Reassessing Martinellimentioning
confidence: 99%
“…Indeed, we agree that people’s perception of the policy is influenced more clearly by evidence of impact 5 and by the salience of that impact to their circumstances. 78 Moreover, ethical concerns may seem moot. Given that UBI is intended to be ‘basic’ rather than comprehensive, it is unclear that it can promote any one particular ‘good’ life.…”
Section: Conclusion: the Practical Importance Of Understanding Ethicsmentioning
confidence: 99%